Magnetic field concentration assisted by epsilon-near-zero media. (28th March 2017) - Liberal, Iñigo; Li, Yue; Engheta, Nader
Abstract : Strengthening the magnetic response of matter at optical frequencies is of fundamental interest, as it provides additional information in spectroscopy, as well as alternative mechanisms to manipulate light at the nanoscale. Here, we demonstrate theoretically that epsilon-near-zero (ENZ) media can enhance the magnetic field concentration capabilities of dielectric resonators. We demonstrate that the magnetic field enhancement factor is unbounded in theory, and it diverges as the size of the ENZ host increases. In practice, the maximal enhancement factor is limited by dissipation losses in the host, and it is found via numerical simulations that ENZ hosts with moderate losses can enhance the performance of a circular dielectric rod resonator by around one order of magnitude. The physical mechanism behind this process is the strongly inhomogeneous magnetic field distributions induced by ENZ media in neighbouring dielectrics. We show that this is an intrinsic property of ENZ media, and that the occurrence of resonant enhancement is independent of the shape of the host. These results might find applications in spectroscopy, in sensing, in light emission and, in general, in investigating light–matter interactions beyond electric dipole transitions. This article is part of the themed issue 'New horizons for nanophotonics'.